Diagnostic accuracy of covid-19 rapid antigen tests with unsupervised self-sampling in people with symptoms in the omicron period: cross sectional study. (14th September 2022) - Schuit, Ewoud; Venekamp, Roderick P; Hooft, Lotty; Veldhuijzen, Irene K; van den Bijllaardt, Wouter; Pas, Suzan D; Zwart, Vivian F; Lodder, Esther B; Hellwich, Marloes; Koppelman, Marco; Molenkamp, Richard; Wijers, Constantijn J H; et al.
Abstract: Objective: To assess the performance of rapid antigen tests with unsupervised nasal and combined oropharyngeal and nasal self-sampling during the omicron period. Design: Prospective cross sectional diagnostic test accuracy study. Setting: Three public health service covid-19 test sites in the Netherlands, 21 December 2021 to 10 February 2022. Participants: 6497 people with covid-19 symptoms aged ≥16 years presenting for testing. Interventions: Participants had a swab sample taken for reverse transcription polymerase chain reaction (RT-PCR, reference test) and received one rapid antigen test to perform unsupervised using either nasal self-sampling (during the emergence of omicron, and when omicron accounted for >90% of infections, phase 1) or with combined oropharyngeal and nasal self-sampling in a subsequent (phase 2; when omicron accounted for >99% of infections). The evaluated tests were Flowflex (Acon Laboratories; phase 1 only), MPBio (MP Biomedicals), and Clinitest (Siemens-Healthineers). Main outcome measures: The main outcomes were sensitivity, specificity, and positive and negative predictive values of each self-test, with RT-PCR testing as the reference standard. Results: During phase 1, 45.0% (n=279) of participants in the Flowflex group, 29.1% (n=239) in the MPBio group, and 35.4% ((n=257) in the Clinitest group were confirmatory testers (previously tested positive by a self-test at own initiative). Overall sensitivities with nasal self-sampling were 79.0% (95% confidence interval 74.7% to 82.8%) for Flowflex, 69.9% (65.1% to 74.4%) for MPBio, and 70.2% (65.6% to 74.5%) for Clinitest. Sensitivities were substantially higher in confirmatory testers (93.6%, 83.6%, and 85.7%, respectively) than in those who tested for other reasons (52.4%, 51.5%, and 49.5%, respectively). Sensitivities decreased from 87.0% to 80.9% (P=0.16 by χ 2 test), 80.0% to 73.0% (P=0.60), and 83.1% to 70.3% (P=0.03), respectively, when transitioning from omicron accounting for 29% of infections to >95% of infections. During phase 2, 53.0% (n=288) of participants in the MPBio group and 44.4% (n=290) in the Clinitest group were confirmatory testers. Overall sensitivities with combined oropharyngeal and nasal self-sampling were 83.0% (78.8% to 86.7%) for MPBio and 77.3% (72.9% to 81.2%) for Clinitest. When combined oropharyngeal and nasal self-sampling was compared with nasal self-sampling, sensitivities were found to be slightly higher in confirmatory testers (87.4% and 86.1%, respectively) and substantially higher in those testing for other reasons (69.3% and 59.9%, respectively). Conclusions: Sensitivities of three rapid antigen tests with nasal self-sampling decreased during the emergence of omicron but was only statistically significant for Clinitest. Sensitivities appeared to be substantially influenced by the proportion of confirmatory testers. Sensitivities of MPBio and Clinitest improved after the addition of oropharyngeal to nasal self-sampling. A positive self-test result justifies prompt self-isolation without the need for confirmatory testing. Individuals with a negative self-test result should adhere to general preventive measures because a false negative result cannot be ruled out. Manufacturers of MPBio and Clinitest may consider extending their instructions for use to include combined oropharyngeal and nasal self-sampling, and other manufacturers of rapid antigen tests should consider evaluating this as well.